Plan de mejoramiento para la empresa Surtitiendas Gaby dedicada a la comercialización y distribución de productos alimenticios de la canasta familiar, en la ciudad de Armenia Quindío con el propósito de ampliar y fidelizar el mercado. (2013)
This paper presents the improvement plan for Gaby Surtitiendas company dedicated to the marketing and distribution of products in the basket, which has a large percentage of customers, which are the shopkeepers and small traders which are seen as the market leading retailer and one of the major sources of the country's economy. This company can identify several shortcomings affecting the organizational structure, sales and strategic planning. The proposed improvement plan, it is helpful for this company as they evaluate the sales and marketing methods that are being implemented, and whether they are adequate or that implementation should be done, as a tool for planning, directing, controlling and assess the administrative processes of each area that aims to strengthen the comprehensive development, in order to increase performance and gain an important position in the market Quindiano; The result of this will help to make improvements and changes in the organizational structure of the company. As it seeks to clarify the behavior of products on the market to consumers and competition, to know whether the needs of customers, distributors and suppliers are satisfied and if it fulfills the requirements demanded by them